Critical review of GSM network structure - Sukhno, P.; Sotnik, S. (ХНУРЕ, 2024)
In world where technology is changing at speed of light, GSM remains unchanging foundation of mobile communications. The study dives into heart of system, revealing its “anatomy and physiology”. Each component of GSM, from Mobile Station to Operation Support System, is studied in detail, showing how coordinated work of all parts allows billions of people to communicate over distance. This work not only reveals mechanisms of GSM, but also looks boldly into future. It outlines problems that this technology faces in whirlwind of modern innovation and proposes solutions for its adaptation. The study lifts veil on challenges facing GSM in world of 5G and IoT and inspires us to find ways to harmoniously coexist past and future in telecommunications. This review is compass for those who want to understand how to keep legacy systems relevant in world that is constantly moving forward. The paper suggests that we think about how we can modernize time-tested technology without losing its reliability and versatility.
Keywords: GSM; OSS; network architecture; mobile communications; time division multiple access